(untitled) (Annals of Medical Research, 2021)
Aim: Alzheimer’s disease is the most common type of dementia. The number of patients with Alzheimer’s is expected to reach 115 million in 2050. Due to the low effectiveness and frequent adverse effects of current treatment approaches, expected results cannot be obtained in treatment. Vitamin D supplements are reported to have protective effects against Alzheimer’s disease by increasing learning and memory performance. In this study, we aimed to evaluate the effect of vitamin D on learning and memory on cognitive deficits by scopolamine-induced memory impairment model, which is an animal model of AD, in aged rats, as well as evaluating whether the effect changes with age. Materials and Methods: Wistar Albino male rats (Young: 4-5 months old, Aged: 21-22 months old) were used in the study. Vitamin D was given for three weeks at 500 IU/kg; scopolamine was applied 1mg/kg half an hour before behavioral experiments. Modified elevated plus maze and Morris water maze tests was performed to assess cognitive abilities during the fourth week; prefrontal cortices were then removed to assess acetylcholinesterase enzyme activity.Results: Vitamin D administration restored memory impairment in old rats in the Morris water maze; whereas there was no effect in young group. Scopolamine significantly increased the brain prefrontal cortex AchE enzyme activity only in the young rats. Vitamin D did not create a statistically significant change in AChE activity in young rats. on the other hand, a significant increase was detected in the elderly group with vitamin D compared to the age-matched control and scopolamine groups.Conclusion: Our results show that the effectiveness of vitamin D changes with age. Vitamin D may be a safe and effective option in preventing dementia development in the elderly group and improving cognitive dysfunction due to Alzheimer’s disease.